Prediction of early clinical response in patients receiving tofacitinib in the OCTAVE Induction 1 and 2 studies. (November 2021) - Lees, Charlie W.; Deuring, J. Jasper; Chiorean, Michael; Daperno, Marco; Bonfanti, Gianluca; Germino, Rebecca; Brown, Pritha Bhadra; Modesto, Irene; Edwards, Roger A.
Introduction: Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis (UC). Outcome prediction based on early treatment response, along with clinical and laboratory variables, would be very useful for clinical practice. The aim of this study was to determine early variables predictive of responder status in patients with UC treated with tofacitinib. Methods: Data were collected from patients treated with tofacitinib 10 mg twice daily in the OCTAVE Induction 1 and 2 studies (NCT01465763 and NCT01458951). Logistic regression and random forest analyses were performed to determine the power of clinical and/or laboratory variables to predict 2- and 3-point partial Mayo score responder status of patients at Weeks 4 or 8 after baseline. Results: From a complete list of variables measured in OCTAVE Induction 1 and 2, analyses identified partial Mayo score, partial Mayo subscore (stool frequency, rectal bleeding, and Physician Global Assessment), cholesterol level, and C-reactive protein level as sufficient variables to predict responder status. Using these variables at baseline and Week 2 predicted responder status at Week 4 with 84–87% accuracy and Week 8 with 74–79% accuracy. Variables at baseline, Weeks 2 and 4 could predict responder status at Week 8 with 85–87% accuracy. Conclusion: Using a limited set of time-dependent variables, statistical and machine learning models enabled early and clinically meaningful predictions of tofacitinib treatment outcomes in patients with moderately to severely active UC.